Study on extraction of biofuel from selected algae species - Vignesh N , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rising level of pollution and depleting fossil fuels has compelled every nation to seek a clean and abundant fuel source. Thus the demand for clean energy increases concerning the development of industrialization. With a clean, abundant fuel like algae biofuel, this demand can be counteracted. The main motivation behind this research is that a person as simple as a farmer can be profited along with this fuel preparation. This algae biofuel will be one of the key tools to attain sustainable development in the Energy and environment sectors. As algae species are so vast and almost present in every habitat, algae can be used as biomass for biofuel preparation and their nutritional values and ability to perform photosynthesis must be mentioned here. Being a tropical country, India has a great potential to indulge in algae biofuel generation to meet the energy demands. Among the most commonly available and known species of algae, three species were selected for this study. They are Spirogyra sp, Chlorella sp, and Spirulina sp. The process used here is anaerobic digestion and pyrolysis for the extraction of fuel content from the biomass. Among the cultures, chlorella seems to have the best potential for biodiesel production both in terms of nutrients and maintenance & yield and spirogyra for biogas production. Thus the mass culture of chlorella can be done by any person and biomass yield can be matched with the demand for biodiesel production. Although spirogyra undergoes anaerobic digestion and yields biogas, the yield rate was not up to the level of conventional biomass sources for biogas production. Biomasses termed as waste like agricultural, cattle dung and other putrescible wastes are most suitable for biogas production because as it a resource from waste i.e. free from culturing, maintenance, expenses, etc